Community-Based Drinking Water And Sanitation Provision (Pamsimas) In Preventing Outbreaks - Muhammad Naufal; M Halley Yudhistira (UNIVED Press, 2025)
This study aims to provide empirical evidence regarding the impact of the Community-Based Drinking Water and Sanitation Program (Pamsimas) in preventing outbreaks. The research is based on the critical importance of drinking water and sanitation for human life, particularly in the field of health. Using a difference-in-differences (DID) approach with a staggered implementation design, the study finds that the Pamsimas program has not yet demonstrated a significant impact at the level of reducing outbreak probabilities. The effects of the program remain limited to the outcomes level, including changes in community behavior such as a decreased likelihood of using rivers/lakes/ponds/irrigation channels for drinking water, an increased likelihood of individuals using private latrines, and a reduced probability of water contamination in a village.